Individualized Functional Subnetworks Connect Human Striatum and Frontal Cortex. (28th October 2021) - Gordon, Evan M; Laumann, Timothy O; Marek, Scott; Newbold, Dillan J; Hampton, Jacqueline M; Seider, Nicole A; Montez, David F; Nielsen, Ashley M; Van, Andrew N; Zheng, Annie; Miller, Ryland; Siegel, Joshua S; et al.
Abstract: The striatum and cerebral cortex are interconnected via multiple recurrent loops that play a major role in many neuropsychiatric conditions. Primate corticostriatal connections can be precisely mapped using invasive tract-tracing. However, noninvasive human research has not mapped these connections with anatomical precision, limited in part by the practice of averaging neuroimaging data across individuals. Here we utilized highly sampled resting-state functional connectivity MRI for individual-specific precision functional mapping (PFM) of corticostriatal connections. We identified ten individual-specific subnetworks linking cortex—predominately frontal cortex—to striatum, most of which converged with nonhuman primate tract-tracing work. These included separable connections between nucleus accumbens core/shell and orbitofrontal/medial frontal gyrus; between anterior striatum and dorsomedial prefrontal cortex; between dorsal caudate and lateral prefrontal cortex; and between middle/posterior putamen and supplementary motor/primary motor cortex. Two subnetworks that did not converge with nonhuman primates were connected to cortical regions associated with human language function. Thus, precision subnetworks identify detailed, individual-specific, neurobiologically plausible corticostriatal connectivity that includes human-specific language networks.